Bladder Cancer and Urothelial Impairment: The Role of TRPV1 as Potential Drug Target. (8th May 2014) - Mistretta, Francesco; Buffi, Nicolò Maria; Lughezzani, Giovanni; Lista, Giuliana; Larcher, Alessandro; Fossati, Nicola; Abrate, Alberto; Dell'Oglio, Paolo; Montorsi, Francesco; Guazzoni, Giorgio; Lazzeri, Massimo
Abstract : Urothelium, in addition to its primary function of barrier, is now understood to act as a complex system of cell communication that exhibits specialized sensory properties in the regulation of physiological or pathological stimuli. Furthermore, it has been hypothesized that bladder inflammation and neoplastic cell growth, the two most representative pathological conditions of the lower urinary tract, may arise from a primary defective urothelial lining. Transient receptor potential vanilloid channel 1 (TRPV1), a receptor widely distributed in lower urinary tract structures and involved in the physiological micturition reflex, was described to have a pathophysiological role in inflammatory conditions and in the genesis and development of urothelial cancer. In our opinion new compounds, such as curcumin, the major component of turmeric Curcuma longa, reported to potentiate the effects of the chemotherapeutic agents used in the management of recurrent urothelial cancer in vitro and also identified as one of several compounds to own the vanillyl structure required to work like a TRPV1 agonist, could be thought as complementary in the clinical management of both the recurrences and the inflammatory effects caused by the endoscopic resection or intravesical chemotherapy administration or could be combined with adjuvant agents to potentiate their antitumoral effect.